Mechanical assessment of trabecular bone stiffness using hybrid skeleton and finite element analysis. Issue 6 (1st November 2016) - Almhdie-Imjabber, Ahmad; Hambli, Ridha; Touvier, Jérôme; Rozenbaum, Olivier; Lespessailles, Eric; Jennane, Rachid
Abstract : The form primitives of trabecular bone can be modelled as a complex structure of rods and plates. The classification of these primitives helps in simulating the physical or mechanical properties which are usually determined not only by the porosity of the object, but also by the arrangement of structure primitives in the 3D space. Based on the classified trabecular bone primitives, we propose in this work a finite element model that is both simple and fast while preserving the accuracy of the analysis. Rods are modelled as beams with circular cross sections. For the plate-like primitives, a triangulation method is used to characterise the behaviour of the corresponding shell elements. Using the proposed method, multiple features can be generated and combined in a statistical discriminant analysis in order to study the mechanical behaviour of selected trabecular bone samples. A clinical study was conducted on two populations of arthritic and osteoporotic bone samples. The results show the ability of our beam/shell model to discriminate the two populations.